Understanding the 'Anorexic Voice' in Anorexia Nervosa. (20th July 2016) - Pugh, Matthew; Waller, Glenn
Abstract : In common with individuals experiencing a number of disorders, people with anorexia nervosa report experiencing an internal 'voice'. The anorexic voice comments on the individual's eating, weight and shape and instructs the individual to restrict or compensate. However, the core characteristics of the anorexic voice are not known. This study aimed to develop a parsimonious model of the voice characteristics that are related to key features of eating disorder pathology and to determine whether patients with anorexia nervosa fall into groups with different voice experiences. The participants were 49 women with full diagnoses of anorexia nervosa. Each completed validated measures of the power and nature of their voice experience and of their responses to the voice. Different voice characteristics were associated with current body mass index, duration of disorder and eating cognitions. Two subgroups emerged, with 'weaker' and 'stronger' voice experiences. Those with stronger voices were characterized by having more negative eating attitudes, more severe compensatory behaviours, a longer duration of illness and a greater likelihood of having the binge–purge subtype of anorexia nervosa. The findings indicate that the anorexic voice is an important element of the psychopathology of anorexia nervosa. Addressing the anorexic voice might be helpful in enhancing outcomes of treatments for anorexia nervosa, but that conclusion might apply only to patients with more severe eating psychopathology. Copyright © 2016 John Wiley & Sons, Ltd. Key Practitioner Message: Experiences of an internal 'anorexic voice' are common in anorexia nervosa. Clinicians should consider the role of the voice when formulating eating pathology in anorexia nervosa, including how individuals perceive and relate to that voice. Addressing the voice may be beneficial, particularly in more severe and enduring forms of anorexia nervosa. When working with the voice, clinicians should aim to address both the content of the voice and how individuals relate and respond to it.